Predictors of evidence-based psychotherapy initiation among veterans with co-occurring PTSD and substance use disorder - Somohano, Vanessa C.; Cameron, David; Lewis, Meaghan M.; O’Neill, Allison; Phillips, Rachel; Kaplan, Joshua; O’Neil, Maya E. (Frontiers in Psychiatry, 2024)
Objective: To compare initiation of PTSD evidence-based psychotherapy (EBP) between Veterans with and without a co-occurring Substance Use Disorder (SUD), and identify factors associated with EBP initiation among Veterans with PTSD-SUD. Method: A national sample of Veterans with PTSD (n = 301,872) and PTSD-SUD (n = 94,515) were identified from VA Electronic Health Record data. Treatment initiation was defined as having at least one mental health encounter associated with Cognitive Processing Therapy or Prolonged Exposure therapy.Generalized estimating equations were used to compare EBP initiation between Veterans with and without co-occurring SUD, and to identify patient-and facility characteristics associated with EBP initiation among Veterans with PTSD-SUD. Results: The majority of Veterans were 30 -44 years old, male sex, and Non-Hispanic White. No significant differences were observed in EBP initiation between Veterans with and without a co-occurring SUD (OR=1.00, p=0.985).Among Veterans with PTSD-SUD, co-occurring bipolar disorder (OR=0.83, p=.000), cooccurring psychotic disorder (OR=0.69, p=.000), service connection (OR=0.94, p=.001), female sex (OR=0.87, p=.000), and being 60 years or older (OR=0.57, p=.000) were associated with a reduced likelihood of initiating a PTSD EBP. Having a co-occurring anxiety disorder (OR=1.06, p=.020), MST history (OR=1.95, p=.000), and high risk for suicide (OR=1.15, p=.000) were associated with an increased likelihood of initiating EBP. Discussion: These findings support VA provision of EBP for Veterans with PTSD regardless of the presence of co-occurring SUD.